1995
DOI: 10.1007/bf02457208
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy of opal matrices with CdS embedded in its pores: Quantum confinement and photonic band gap effects

Abstract: ricevuto il 6 Settembre 1995) PACS 71.35 -Excitons and related phenomena (including electron-hole drops). PACS 78.66.Hf-II-VI semiconductors. PACS 42.25.Bs -Wave propagation, transmission and absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(96 citation statements)
references
References 8 publications
2
88
0
6
Order By: Relevance
“…The spectral width of the PSB is dependent on refractive index contrast and can be changed by filling the voids of opal with suitable substances [60]. Modern technology allows to fill opal voids with various dielectrics [61], semiconductors [38,60], liquid crystals [62], and metals [63].…”
Section: Artificial Opalsmentioning
confidence: 99%
“…The spectral width of the PSB is dependent on refractive index contrast and can be changed by filling the voids of opal with suitable substances [60]. Modern technology allows to fill opal voids with various dielectrics [61], semiconductors [38,60], liquid crystals [62], and metals [63].…”
Section: Artificial Opalsmentioning
confidence: 99%
“…Dark aggregations around them correspond to semiconductor inclusions. Additional studies [18] have shown that a size of CdS crystallites (average value ~10 nm) is bigger than the exciton Bohr radius in this material (αB = 2.8 nm). Consequently, the semiconductor phase occurs in the so-called regime of weak quantum confinement [19].…”
Section: Sample Preparation and Characterizationmentioning
confidence: 69%
“…The PI of this project [VA] came to this area with a strong background in studies of synthetic opals [23][24][25][26][27][28] which are 3D lattices of silica nanospheres. In addition the PI [VA] had an extensive experience in studies of photonic crystal waveguides [29][30][31][32][33][34] and semiconductor microcavities [35][36][37][38] .…”
Section: Statement Of the Problem Studiedmentioning
confidence: 99%